EFFECT OF BRAND EQUITY ANALYSIS ON HONDA MOTORCYCLE PURCHASE DECISION IN MEDAN CITY - Nursaimatussaddiya, Nursaimatussaddiya; Habibie, Muhammad; Meisya Aziti, Tria (JOEL: Journal of Educational and Language Research, 2022)
This study aims to determine: 1) The magnitude of the influence of brand equity on Motorcycle Purchase Decisions at Honda Sau Sin Power Motor Dealers. 2) The level of buyer satisfaction with the marketing of Honda motorcycles at CV. Sau Sin Power Motor. The instrument analysis technique in this study used simple linear regression analysis and the determinant coefficient test. So the results of this study are 1) Brand Equity has a positive effect on purchasing decisions for Honda motorcycles in Medan City with a CV case study. Sau Sin Power Motor Medan. 2) Characteristics of the respondents in this case the consumers of Honda motorcycle buyers in CV. The majority of Sau Sin Power Motor Medan are male, and with the age of 31 – 40 years with self-employed jobs. This study aims to determine: 1) The magnitude of the influence of brand equity on Motorcycle Purchase Decisions at Honda Sau Sin Power Motor Dealers. 2) The level of buyer satisfaction with the marketing of Honda motorcycles at CV. Sau Sin Power Motor. In this study, using the sampling technique is non-random sampling with the Solvin method with the respondent's criterion is consumers who buy Honda motorbikes at CV. Sau Sin Power Motor. This study used a sample of 80 respondents. The instrument analysis technique in this study uses simple linear regression analysis and the coefficient of determinant test. So that the results of this study are 1) Brand Equity has a positive effect on purchasing decisions for Honda motorbikes in Medan with a case study CV. Sau Sin Power Motor Medan. 2) Characteristics of respondents, in this case, consumers who buy Honda motorbikes at CV. The majority of Sau Sin Power Motor Medan are male, and those aged 31-40 years old work as entrepreneurs